IMPACTS OF PERCEIVED SEVERITY OF SICKNESS AND BENEFIT OF TREATMENT ON COMPLIANCE OF LEPROSY PATIENTS IN SOKOTO STATE (1988)
The purpose of this study was to investigate the impacts of perceived severity of sickness and benefit of treatment in relation to compliance to treatment of leprosy patients in Sokoto State. The study also looked into the interactive effects of perceived severity of sickness and benefit of treatment on compliance of the various groups of leprosy patients in the state. Nine sub-hypotheses were stated to guide the study towards finding an answer to the main hypothesis. Using the cluster sampling technique, 952 randomly selected subjects from Argungu, Sokoto and Zuru administrative divisions of Sokoto State were used for the study. The main research instrument for the study was the structured interview. The interviews were conducted by the researcher with the aid of six selected and trained assistants. The chi-square x(2) was used to test the sub-hypotheses at a significant level of 0.05. The x(2) was however corroborated by the descriptive statistics (percentages). The findings of the study revealed that the higher the level of perceived severity of sickness, the lower the compliance rate. However, with regards to perceived benefit of treatment, the higher the perception, the higher the compliance rate. The percentages for compliance in the case of perceived severity of sickness were 40.4% for those who perceived leprosy very severe, 49.9% and 54.9% for those who perceived leprosy moderately severe and not severe respectively. The percentages for compliance in the case of perceived benefit of treatment were 90.6%, 73.8% and 19% for those who perceived treatment very beneficial, somewhat beneficial and not beneficial respectively. The result showed that those who perceived treatment very beneficial complied to treatment more than those who perceived the disease very severe. Similarly, those who perceived treatment somewhat beneficial were better compilers than those who perceived the disease moderately severe. However, those who perceived the disease not severe were better compilers than those who perceived treatment not beneficial. Based upon the findings of this study, the researcher recommended among other things, a wide and effective public enlightment on the various aspects of leprosy and people should be made to realised that leprosy is curable, it is not a very severe disease, it doesn't kill it only cripples the victim if treatment is delayed